2015
DOI: 10.1097/qai.0000000000000438
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Respondent-Driven Sampling as an Implementation Tool for Universal Coverage of Antiretroviral Studies Among Men Who Have Sex With Men Living With HIV

Abstract: Introduction The TRUST model based on experimental and observational data posits that integration of HIV prevention and universal coverage of antiretroviral treatment (UCT) at a trusted community venue provides a framework for achieving effective reduction in HIV-related morbidity and mortality among men who have sex with men (MSM) living with HIV as well as reducing HIV incidence. The analyses presented here evaluate the utility of respondent-driven sampling (RDS) as an implementation tool for engaging MSM in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 38 publications
2
66
0
Order By: Relevance
“…For example, in some study sites respondents in later recruitment waves reported less knowledge about HIV transmission and less frequent HIV testing, which is consistent with findings from MSM in Nigeria 14. RDS could potentially be used as a peer-driven intervention to disseminate HIV prevention knowledge and testing behaviours from earlier to later waves of MSM.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…For example, in some study sites respondents in later recruitment waves reported less knowledge about HIV transmission and less frequent HIV testing, which is consistent with findings from MSM in Nigeria 14. RDS could potentially be used as a peer-driven intervention to disseminate HIV prevention knowledge and testing behaviours from earlier to later waves of MSM.…”
Section: Discussionsupporting
confidence: 80%
“…If seeds are selected based on a specific trait, for instance connection to an MSM CBO, the early wave recruits will likely share characteristics similar to those of the seeds. Because of this, earlier-recruited as compared with later-recruited participants may have varying levels of sexual orientation-related stigma and engagement in the HIV care continuum, and therefore may also have different intervention needs upon presentation to a study site 14. Making use of RDS recruitment to reach MSM who are less exposed to intervention programmes could be beneficial for improving MSM-related programme outreach, particularly if these men are less likely to know their HIV status or less likely to be previously engaged in care.…”
Section: Introductionmentioning
confidence: 99%
“…Another potential concern is whether the study oversampled those already engaged in care. RDS leverages peer networks to try and reach those currently not reached by services,30 and in this study two-thirds of women reached had not engaged in mobile HIV testing or care services in the past 12 months. Finally, interpretations of associations with ART use are limited by the cross-sectional nature of the data and potentially missing measures of structural barriers to care; larger, prospective cohorts are needed to causally assess predictors of ART use and retention and should further evaluate potential barriers such as housing, food security and primary work venues not included in our assessment.…”
Section: Discussionmentioning
confidence: 84%
“…Our data also showed similarities with other RDS data from MSM in sub-Saharan Africa. Baral et al 28 demonstrated in a study from Nigeria that RDS could be used as a method of engaging MSM in antiretroviral therapy services. Models of engagement of MSM such as the SPEND model ((P) Pharmacies as treatment sources; (E) Educate health professionals; (N) Navigation for patients who must access the health system; and (D) Discrimination reduction), which integrates the RDS approach to increase MSM awareness of available services that are trusted, access such networks 29.…”
Section: Discussionmentioning
confidence: 99%